Differences in Stress Levels Before and After Deep Breathing Relaxation Techniques Were Given to Nursing Students - Wadu, Tomi Lorenzo Kana; Siagian, Nurhayati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The prevalence of students experiencing stress in Indonesia ranges from 36.7-71.6%. One method that can be used to overcome stress is alternative therapy, such as deep breathing. Therefore, this researcher aims to analyze the difference in stress levels before and after being given a breathing relaxation technique in nursing students at the Adventist University of Indonesia in facing final semester exams. This type of research is an experimental study using the One-Group Pretest-Posttest Design. The results found that the initial stress levels of students showed variations ranging from normal to very severe categories, so that respondents had varying stress conditions before the intervention was carried out. There was a decrease in stress scores after being given the deep breathing relaxation technique, as seen from a decrease in the average post-test score compared to the pre-test. The results of the Wilcoxon Signed Rank Test showed a p-value of 0.059, so the decrease in stress was not statistically significant. Overall, deep breathing has potential as a stress management method, but its effectiveness in this study has not been proven significant.